Cartographies of Diasporic Thinking (2020)
Inspired by Judith Butler’s critique of Zionism, this article explores one artistic practice that may be considered as developing a diasporic thinking that is specifically rooted in the experience of forced displacement in Colombia. We concentrate on an artwork of Colombian artist Libia Posada as an example of the attempt to embody experiences of dispossession and eviction that goes beyond the simple acknowledgment of victimhood that has characterized the work of state institutions in dealing with displaced populations. In her installation, titled Signos cardinales (Cardinal Signs), Posada presents a series of photographs of displaced women’s feet and legs. On these bodily parts, Posada has drawn a map detailing the journey each of these women was forced to take from her native land to a different part of the country, during the armed conflict that has been affecting Colombia since the second half of the twentieth century. We focus on what we believe is the “content” of the diasporic thinking conveyed by this artwork: (1) re-inscribing a memory of displacement, thus aiming at a double exercise of re-appropriation and transformation of identity; and (2) creating a counter-genealogy of the production of space, which in the case of Signos cardinales is concretely established as what we call a “counter-cartography.”. © 2020, © 2020 International Society for the Study of European Ideas.